2022
DOI: 10.1002/elan.202100704
|View full text |Cite
|
Sign up to set email alerts
|

On the Counter‐intuitive Heterogeneous Electron Transfer Barrier Properties of Alkanethiolate Monolayers on Gold: Smooth versus Rough Surfaces

Abstract: Alkanethiolate monolayers formed on rough gold surfaces can, somewhat surprisingly, act as stronger barriers to heterogeneous electron transfer than those on smooth gold surfaces. This paper presents a possible explanation for this observation by constructing simple geometric models of a "rough" and "smooth" gold surface to examine how microscopic roughness differences can affect the nucleation/growth of the adlayer and size/density of structural defects. Expectedly, the number of defects predicted for adlayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Not only do longer alkylthiolate chains increase the electron-tunneling distance across the monolayer but, given that longer monolayers also pack better, 31,32 there are also less defects in the monolayer, which are necessary to some degree to support efficient electron transfer. 14,33 Traditional electrochemical aptamer sensors predominantly employ the hydroxyl-terminated alkylthiolate 6-mercapto-1hexanol (MCH) as the passivating blocking layer molecule to backfill unoccupied gold atoms after aptamer immobilization. 34 MCH has previously been demonstrated to be somewhat sufficient for reducing nonspecific adsorption and mitigating unwanted redox processes (e.g., oxygen reduction) while still allowing for robust electron transfer and offering moderate stability for multihour deployment.…”
Section: Acsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only do longer alkylthiolate chains increase the electron-tunneling distance across the monolayer but, given that longer monolayers also pack better, 31,32 there are also less defects in the monolayer, which are necessary to some degree to support efficient electron transfer. 14,33 Traditional electrochemical aptamer sensors predominantly employ the hydroxyl-terminated alkylthiolate 6-mercapto-1hexanol (MCH) as the passivating blocking layer molecule to backfill unoccupied gold atoms after aptamer immobilization. 34 MCH has previously been demonstrated to be somewhat sufficient for reducing nonspecific adsorption and mitigating unwanted redox processes (e.g., oxygen reduction) while still allowing for robust electron transfer and offering moderate stability for multihour deployment.…”
Section: Acsmentioning
confidence: 99%
“…Recent literature has shown that the roughness of the gold is resultingly critical for monolayer stability, as smaller gold step edges force smaller-sized monolayer defects compared to those on highly smooth gold or even monocrystalline gold surfaces. 14 However, even with an appropriate gold roughness for minimizing monolayer defect size (Figure 1a2), thermal desorption of the monolayer still remains a significant challenge. Moving to body temperature and/or complex biofluids further increases desorption through increased thermal energy and/or the presence of foulants that provide an "energetic bridge" to reduce the single-step energy needed for desorption (Figure 1a3).…”
Section: Overview Of Proposed Mechanisms Of Mixed Monolayer Degradati...mentioning
confidence: 99%
“…This demonstrates that biofouling alters electron transfer kinetics with the electrode surface, either in the analyte-bound or unbound states for aptamer molecules, which is consistent with results seen in the literature where the frequency of maximum electron transfer for the unbound aptamer is shown to shift during the initial 2-3 hour exponential fouling phase. 16 Initial fouling likely occurs at monolayer defects 14,40 leading to an increased charge transfer resistance, which would explain both the initial reduction in redox tag current and the initial shift in the frequency of maximum electron transfer toward lower SWV frequencies, as expected from the Lovrić formalism. 45 Over multiple days, desorption of passivation molecules allows for replacement with foulants and rearrangement of the biofouled layer into a highly defective film, a process that occurs much more rapidly on MCH sensors than MCO sensors as previously discussed.…”
Section: Resultsmentioning
confidence: 92%
“…Surprisingly, nanoscale roughened gold provides greater monolayer stability, as smaller gold step edges force smallersized monolayer defects compared to highly smooth gold or even monocrystalline gold. 14 However, even with the surface of a smooth gold electrode appropriately roughened to minimize monolayer defect size (Figure 1a2), thermal desorption of the monolayer still remains a significant challenge. As further shown in Figure 1a3, moving to body temperature and/or complex biofluids further increases desorption through increased thermal energy and/or presence of foulants that provide an 'energetic bridge' to reduce the single-step energy needed for desorption (Figure 1a3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation